A Pilot Genome‐Wide Analysis Study Identifies Loci Associated With Response to Obeticholic Acid in Patients With NASH. Issue 12 (3rd November 2019) - Gawrieh, Samer; Guo, Xiuqing; Tan, Jingyi; Lauzon, Marie; Taylor, Kent D.; Loomba, Rohit; Cummings, Oscar W.; Pillai, Sreekumar; Bhatnagar, Pallav; Kowdley, Kris V.; Yates, Katherine; Wilson, Laura A.; et al.
Abstract : A significantly higher proportion of patients with nonalcoholic steatohepatitis (NASH) who received obeticholic acid (OCA) had histological improvement relative to placebo in the FLINT (farnesoid X nuclear receptor ligand obeticholic acid for noncirrhotic, NASH treatment) trial. However, genetic predictors of response to OCA are unknown. We conducted a genome‐wide association study (GWAS) in FLINT participants to identify variants associated with NASH resolution and fibrosis improvement. Genotyping was performed using the Omni2.5 content GWAS chip. To avoid false positives introduced by population stratification, we focused our GWAS on white participants. Six regions on chromosomes 1, 4, 6, 7, 15, and 17 had multiple single nucleotide polymorphisms (SNPs) with suggestive association ( P < 1 × 10 - 4 ) with NASH resolution. A sentinel SNP, rs75508464, near CELA3B on chromosome 1 was associated with NASH resolution, improvement in the nonalcoholic fatty liver disease activity score, portal inflammation, and fibrosis. Among individuals carrying this allele, 83% achieved NASH resolution with OCA compared with only 33% with placebo. Eight regions on chromosomes 1, 2, 3, 11, 13, and 18 had multiple SNPs associated with fibrosis improvement; of these, rs12130403 near TDRD10 on chromosome 1 was also associated with improvement in NASH and portal inflammation, and rs4073431 near ANO3 on chromosome 11 was associated with NASH resolution and improvement in steatosis. Multiple SNPs on chromosome 11 had suggestive association with pruritus, with rs1379650 near ANO5 being the top SNP. Conclusion: We identified several variants that may be associated with histological improvement and pruritus in individuals with NASH receiving OCA. The rs75508464 variant near CELA3B may have the most significant effect on NASH resolution in those receiving OCA. Abstract : We conducted a genome wide association study (GWAS) in FLINT trial participants to identify variants associated with NASH resolution and fibrosis improvement. We identified several variants associated with histological improvement and pruritus in individuals with NASH receiving obeticholic acid (OCA). The rs75508464 variant near CELA3B had the most significant effect on NASH resolution in those receiving OCA.